Efficiency analysis of tank-type water distillation system integrated with hot water collector - El, Emin; Cakmak, Gulsah; Yildiz, Cengiz (Elsevier, 2017)
In this study, besides the hot water, it was also aimed to obtain distilled water from solar still water heating systems, which are widely used in obtaining hot water. For this purpose, a new type of distiller was obtained by making modifications, which enable us to obtain distilled water, on a solar still water heating system having flat-surface panel collector and vertical tank and operating as a closed system. The designed system was tested under both natural convection and forced convection at flow rates of 30 kg/h and 50 kg/h. As a result of performed experiments, the temperature, productivity, and distilled water production amounts were calculated for the designed system. It was determined that the temperature of hot water obtained was sufficient for daily use. According to the results, as the highest amount of water, 1.820 kg/day distilled water was obtained form also the natural convection system. In order to determine the drinkability of distilled water, the laboratory analyses were carried out, and it was found that the water meets EC standards. Thus, the clean and hot water was obtained at the same time from the designed system under real weather conditions. (C) 2017 Published by Elsevier Ltd.
Keywords: Solar still; Energy efficiency; Drinking water; Tank type distiller